DIFFERENTIAL DIAGNOSTICS OF FACE MYOFASCIAL PAIN SYNDROME WITH TYPICAL TRIGEMINAL NEURALGIA (A CLINICAL CASE REPORT) - E. V. Balyazina; T. A. Isahanova (Медицинский вестник Юга России, 2016)
A case of face myofascial pain syndrome of female patient 54 years old is discussed. The diagnostics criteria, including clinical and neurological examination, computerized  tomography  of brain, facial bones and temporomandibular  joints, diagnostic blockade are described. Treatment issues are discussed.